Development and Analysis of a Novel Magnetic Levitation System with a Feedback Controller for Additive Manufacturing Applications - Parichit Kumar; Mir Behrad Khamesee (Actuators, 2022)
The primary goal of this study is to create a magnetic levitation system for additive manufacturing (AM) applications. The emphasis of this research is placed on Laser Directed Energy Deposition via Powder Feeding (LDED-PF). The primary benefit of using a magnetic levitation system for AM applications is that the levitated geometry is expected to be a portion of the final part manufactured, thus eliminating the need for a substrate and reducing the post-processing operation requirement. Two novel levitation systems were designed, optimized, and manufactured. The design, optimization, and analysis were first conducted in the simulation environment using ANSYS Maxwell and then tested with experiments. The newly developed systems depicted a much-improved performance compared to the first prototype developed in a previous article written by the authors. The newly developed systems had an increase in levitation height, the surface area for powder deposition activities, the time available for AM operations, and the ability to support additional mass within the limits of allowable inputs. The compatibility of the levitation system with AM applications was also verified by testing the impact of powder deposition and the ability of the levitated disc to support added mass as a function of time with minimal loss in performance. This article also highlights the development of a novel feedback PID controller for the levitation system. To improve the overall performance of the controller, a feedforward controller was added in conjunction with the PID controller. Finally, the levitation system was shown to highlight control over levitation height and maintain constant levitation height with the addition of an added mass using the feedback controller.